Multi-Facet Critical Review of Autonomous Vehicles in India - Deshpande, Ashutosh (Digital Repository of Theses, 2025)
This research study will benefit the reader to gain deeper understanding about autonomous vehicles in Indian context in multi facet review. Secondary research is conducted via PESTLE model and Primary research is conducted via mixed methodology approach. Quantitative method using survey as a tool to understand awareness and perceptions of individuals on multiple facets of autonomous vehicles in India. Qualitative method using guided interview as a tool to understand views and opinions of specific stakeholders of the value chain of the mutual impact of autonomous vehicles in India.